Aktywność fizyczna i zdrowie polskiej młodzieży jako wartości - Dudkowski-Sadowska, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
In recent years, there has been a decline in physical activity rates among Polish youth, which may have a negative impact on health: only 15.6% of students aged 11–18 met the criteria of the World Health Organization, taking daily exercises for at least 60 minutes in total. The aim of the study is to try to answer the question whether young people perceive health and physical activity as important values, or whether the quoted data clearly prove their low position in the young people’s axiologies. The basis for considerations is a review of research results, primarily in the field of psychology and sociology, indicating the unsystematic analysis of the importance of health and physical activity for young people; the high, but not the highest, position of health and the occasional recognition of physical activity as a value.